Sdd3 regulates the biofilm formation of Candida albicans via the Rho1-PKC-MAPK pathway - Li Mei Pang; Guisheng Zeng; Eve Wai Ling Chow; Xiaoli Xu; Ning Li; Yee Jiun Kok; Shu Chen Chong; Xuezhi Bi; Jiaxin Gao; Chaminda Jayampath Seneviratne; Yue Wang (mBio)
ABSTRACT Candida albicans, the most frequently isolated fungal pathogen in humans, forms biofilms that enhance resistance to antifungal drugs and host immunity, leading to frequent treatment failure. Understanding the molecular mechanisms governing biofilm formation is crucial for developing anti-biofilm therapies. In this study, we conducted a genetic screen to identify novel genes that regulate biofilm formation in C. albicans. One identified gene is ORF19.6693, a homolog of the Saccharomyces cerevisiae SDD3 gene. The sdd3∆/∆ mutant exhibited severe defects in biofilm formation and significantly reduced chitin content in the cell wall. Overexpression of the constitutively active version of the Rho1 GTPase Rho1G18V, an upstream activator of the protein kinase C (PKC)-mitogen-activated protein kinase (MAPK) cell-wall integrity pathway, rescued these defects. Affinity purification, mass spectrometry, and co-immunoprecipitation revealed Sdd3’s physical interaction with Bem2, the GTPase-activating protein of Rho1. Deletion of SDD3 significantly reduced the amount of the active GTP-bound form of Rho1, thereby diminishing PKC-MAPK signaling and downregulating chitin synthase genes CHS2 and CHS8. Taken together, our studies identify a new biofilm regulator, Sdd3, in C. albicans that modulates Rho1 activity through its inhibitory interaction with Bem2, thereby regulating the PKC-MAPK pathway to control chitin biosynthesis, which is critical for biofilm formation. As an upstream component of the pathway and lacking a homolog in mammals, Sdd3 has the potential to serve as an antifungal target for biofilm infections.IMPORTANCEThe human fungal pathogen Candida albicans is categorized as a critical priority pathogen on the World Health Organization’s Fungal Priority Pathogens List. A key virulence attribute of this pathogen is its ability to form biofilms on the surfaces of indwelling medical devices. Fungal cells in biofilms are highly resistant to antifungal drugs and host immunity, leading to treatment failure. This study conducted a genetic screen to discover novel genes that regulate biofilm formation. We found that deletion of the SDD3 gene caused severe biofilm defects. Sdd3 negatively regulates the Rho1 GTPase, an upstream activator of the protein kinase C-mitogen-activated protein kinase pathway, through direct interaction with Bem2, the GTPase-activating protein of Rho1, resulting in a significant decrease in chitin content in the fungal cell wall. This chitin synthesis defect leads to biofilm formation failure. Given its essential role in biofilm formation, Sdd3 could serve as an antifungal target for biofilm infections.